Giardia duodenalis infection: risk factors for children living in sub-standard settlements in Brazil - Júlio César Teixeira; Léo Heller; Mauricio L. Barreto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The objective of the present study was to characterize Giardia duodenalis infection among children living in sub-standard settlement areas in the municipality of Juiz de Fora, Minas Gerais State, Brazil. The cross-sectional epidemiological study included 590 children from 1 to 5 years of age. Data were collected from one child per selected family through home interviews with the parent or guardian and parasitological examination of stool samples. Thirty-one putative risk factors concerning family structure, socioeconomic status, and environmental factors were analyzed by multivariate logistic regression. Prevalence of G. duodenalis infection was 18% (106 children). Four potential risk factors were heavily associated with G. duodenalis infection: number of under-five children in the same household, index child's birth order, existence of a bathroom in the home, and drinking water source.